Human performance assessment of a single air traffic controller conducting multiple remote tower operations. Issue 2 (13th November 2019) - Kearney, Peter; Li, Wen‐Chin; Zhang, Jingyi; Braithwaite, Graham; Wang, Lei
Abstract: The innovative concept of multiple remote tower operations (MRTO) can maximize cost savings by applying video panorama‐based remote tower working positions, which can facilitate fewer air traffic controllers (ATCO) to provide the air traffic services (ATS) function for more airports. Five subject‐matter experts, qualified remote tower ATCOs, participated in this research work by applying the human error template (HET) and comparing workload between physical tower operations and MRTO using NASA‐TLX (Task Load Index). The results demonstrate that augmented visualization provided sufficient technical support for a single ATCO to perform tasks originally designed to be performed by four ATCOs, however, the demands of the associated multiple tasks induced significant workload. There were significant differences in ATCOs' mental demand, temporal demand, effort, and frustration between MRTO and physical tower operations. This innovative technology may induce human–computer interaction (HCI) issues that impact ATCO's perceived workload. This creates a need for further research on how to manage ATCO's workload in a multiple remote tower environment. This research work provided scientific evidence that MRTO can achieve the objectives of Single European Sky Air Traffic Management Research program. The findings can be applied to both ATCO training design and remote tower system design.